Implementation of Presentation-Assisted Discovery Learning Model Using Canva Application in IPAS Learning to Improve Learning Outcomes - Dwi Nur Laela; Badarudin Badarudin (Jurnal Pijar MIPA, 2026)
Learning Natural and Social Sciences integrated with regional culture in elementary schools still faces various obstacles, resulting in low student learning outcomes in the cognitive, affective, and psychomotor domains. This problem indicates a gap between the demands of active, meaningful learning and the underdeveloped learning practices, with minimal use of digital media. Therefore, this study aims to determine improvements in fifth-grade student learning outcomes through the implementation of the Discovery Learning model supported by Canva-based presentation media. This study used a collaborative Classroom Action Research (CAR) method, implemented in two cycles, with stages of planning, implementation, observation, and reflection. The research subjects were fifth-grade elementary school students. Data collection techniques included tests, observation, and documentation. Data analysis was conducted using quantitative descriptive techniques, calculating the average learning outcome score for each cycle. The results showed improvements in all domains. The average cognitive learning outcome score increased from 64.81 in Cycle I to 91.48 in Cycle II. The affective domain increased from 66.48 to 90.00, while the psychomotor domain increased from 66.39 to 82.00. This increase occurred because the Discovery Learning model supported by Canva was able to create more interactive learning, encourage student activeness in discovering concepts, and facilitate the visualization of material in an interesting and contextual way. Thus, it can be concluded that the implementation of the Discovery Learning model, supported by Canva, is effective in improving student learning outcomes across the cognitive, affective, and psychomotor domains. The implication of this study is the need for teachers to continuously integrate innovative learning models and digital media to create more meaningful, student-tailored learning.